The Role of the Microbiota in Graves’ Disease and Graves’ Orbitopathy - Hou, Jueyu; Tang, Yunjing; Chen, Yongjiang; Chen, Danian (Frontiers in Cellular and Infection Microbiology, 2021)
The gut microbiota is considered a vital organ of the human body with some crucial functions. Many autoimmune diseases patients, including Graves’ disease (GD) and Graves’ orbitopathy (GO) patients, have abnormal compositions of the microbiota (dysbiosis). Here we discuss recent findings using 16S ribosomal RNA gene sequencing about the microbiome changes in animal models and human patients of GD/GO. The abundance of Lactobacillus, Prevotella, and Veillonella consistently increases in many GD patients. Glucocorticoids (GCs) are the first-line treatment for GO; if no response is observed, immunosuppressants and biologic agents should be considered. Recent studies indicate that therapeutic reagents (including anti-thyroid drugs, glucocorticoids, immunosuppressants, and some biologics) can also affect the gut microbiota. Antigenic mimicry and imbalance of T helper 17 cells (Th17)/regulatory T cells (Tregs) are primary mechanisms proposed for the role of gut microbiota in the pathogenesis of GD/GO. Potential therapeutic protocols targeting the gut microbiota include antibiotics, probiotics, diet modifications, and fecal microbial transplantation. Future studies will reveal the underlying mechanism and its applications in clinical settings.